Clinical outcome of the ovarian clear cell carcinoma compared to other epithelial ovarian cancers when treated with paclitaxel and carboplatin - Daranee Sirichaisutdhikorn (2018)
Ovarian clear cell carcinoma (OCCC) has an aggressive histology. Our aim was to evaluate the progression free survival (PFS) of OCCC patients compared to other epithelial histology patients when treated with surgery followed by carboplatin and paclitaxel (PT) regimen. The medical records of them who treated with PT regimen at Chiang Mai University Hospital between January 2004 and December 2008 were reviewed. 67 ovarian clear cell patients were compared to 121 non-clear cell ovarian cancer patients. The mean age of OCCC patients was younger than that of the non-clear cell group (46.7 vs. 51.2 years old, P=0.001). OCCC patients presented in early stage more often than the non-clear cell group (76.1% vs. 38.0%, P=0.001). The surgical procedures in both groups were not significantly different. The complete response rates of OCCC patients and other epithelial histology patients were 65.7% and 55.3%, respectively (P=0.01). With a mean follow-up time of 25 months, the 3-year PFS rates of OCCC and non-clear cell patients in early stages were not significantly different (65.4% vs. 64.2%, P=0.45). However, in the advanced stage, the 1-year PFS rate of OCCC patients was significantly lower than that of non clear cell patients (6.3% vs. 49.6%, P=0.001). In conclusion, patients were commonly younger and presented in earlier stages than non-clear cell ovarian cancer patients. In early stages, clear cell ovarian cancer patients had similar outcomes to other epithelial ovarian histology patients, whereas the outcome was very poor in advanced stages.